SHEAR BOND STRENGTH OF BRACKETS BONDED TO PORCELAIN SURFACE: IN VITRO STUDY - Fidan Alakuş Sabuncuoğlu; Ergül Ertürk (Istanbul University, 2016)
Purpose: To compare the effects of different porcelain surface treatment methods on the shear bond strength (SBS) and fracture mode of orthodontic brackets. Materials and Methods: Seventy feldspathic porcelain disk samples mounted in acrylic resin blocks were divided into seven groups (n=10) according to type of surface treatment: I, Diamond bur; II, Orthosphoric acid (OPA); III, hydrofluoric acid (HFA); IV, sandblasted with aluminum oxide (SB); V, SB+HFA; VI, Neodymium:yttrium-aluminum-garnet (Nd:YAG) laser; VII, Erbium:yttrium-aluminum-garnet (Er:YAG) laser. Brackets were affixed to treated all-porcelain surfaces with a silane bonding agent and adhesive resin and subjected to SBS testing. Specimens were evaluated according to the adhesive remnant index (ARI), and failure modes were assessed quantitatively under a stereomicroscope and morphologically under a scanning electron microscope (SEM). Statistical analysis was performed using one-way analysis of variance and the post-hoc Tukey test, with the significance level set at 0.05. Results: The highest SBS values were observed for Group V, with no significant difference between Groups V and III. SBS values for Group I were significantly lower than those of all other groups tested. The porcelain/resin interface was the most common site of failure in Group V (40%) and Group III (30%), whereas other groups showed various types of bond failure, with no specific location pre-dominating, but with some of the adhesive left on the porcelain surfaces (ARI scores 2 or 3) in most cases. Conclusion: The current findings indicate that a diamond bur alone is unable to sufficiently etch porcelain surfaces for bracket bonding. Moreover, SB and HFA etching used in combination results in a significantly higher shear-bond strength than HFA or SB alone. Finally, laser etching with either an Nd:YAG or Er:YAG laser was found to be more effective and less time-consuming than both HFA acid and SB for the treatment of deglazed feldspathic porcelain.